KESALAHAN- KESALAHAN GRAMATIKAL DALAM KARYA TULIS MAHASISWA DI FAKULTAS ILMU BUDAYA UNIVERSITAS SAM RATULANGI - Talib, Alisa Annisa; Lasut, Theresia M. C.; Ranuntu, Garryn Ch. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2020)
ABSTRACTÂ Â Â Â Â Â Â Â Â Â Â Â  This skripsi, entitled â€œGrammatical Errors in Studentsâ€™ Writing at Faculty of Humanities Sam Ratulangi Universityâ€, is an attempt to identify, classify and analyze the types of errors in English grammar in descriptive writing made by fourth semesterÂ  students of Faculty of Humanities. The data were collected from the fourth semester studentsâ€™ final test. All data concerning grammatical errors were identified, classified, and analyzed by using Lennonâ€™s theory. The method used in this research was descriptive.Â  The result of this research showed that there are four kinds of errors made by the students. Those four kinds of errors are first, addition as grammatical error by adding a part which is unnecessary; second, omission as grammatical error by eliminating a part which is necessary; third, substitution isÂ  grammatical error by using some grammar to another grammar; the last, ordering as grammatical error by locating some words into wrong order.Â  This research is expected to give a contribution to the study of linguistics and to help students in identifying errors in English that commonly made by Indonesian learners. Â Keywords : Grammar,grammatical, errors, studentsâ€™ writings